2.
а) [tex](a+b)^3-(a+b)(a^{2}-ab+b^2)= a^3+3a^2b+3ab^2+b^3-(a^3+b^3)=[/tex]
[tex]=a^3+3a^2b+3ab^2+b^3-a^3-b^3= 3a^2b+3ab^2[/tex]
Ответ: [tex]3a^2b+3ab^2[/tex]
б) [tex](4a+\frac{1}{2} b-2)^2-2(-b+2ab-8a)=[/tex]
[tex]=16a^2+4ab+\frac{1}{4} b^2-16a-2b+4+2b-4ab+16a=[/tex]
[tex]=16a^2+\frac{1}{4} b^2+4[/tex]
Ответ: [tex]16a^2+\frac{1}{4} b^2+4[/tex]
3.
[tex]-3xy(x+y)-x^3-y^3=-(x^3+3x^2y+3xy^2+y^3)=-(x+y)^3[/tex]
при [tex]x=-35;[/tex] [tex]y=-25[/tex]
[tex]-(-35-25)^3=-(-60)^3=216000[/tex]
Ответ: [tex]216000[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
2.
а) [tex](a+b)^3-(a+b)(a^{2}-ab+b^2)= a^3+3a^2b+3ab^2+b^3-(a^3+b^3)=[/tex]
[tex]=a^3+3a^2b+3ab^2+b^3-a^3-b^3= 3a^2b+3ab^2[/tex]
Ответ: [tex]3a^2b+3ab^2[/tex]
б) [tex](4a+\frac{1}{2} b-2)^2-2(-b+2ab-8a)=[/tex]
[tex]=16a^2+4ab+\frac{1}{4} b^2-16a-2b+4+2b-4ab+16a=[/tex]
[tex]=16a^2+\frac{1}{4} b^2+4[/tex]
Ответ: [tex]16a^2+\frac{1}{4} b^2+4[/tex]
3.
[tex]-3xy(x+y)-x^3-y^3=-(x^3+3x^2y+3xy^2+y^3)=-(x+y)^3[/tex]
при [tex]x=-35;[/tex] [tex]y=-25[/tex]
[tex]-(-35-25)^3=-(-60)^3=216000[/tex]
Ответ: [tex]216000[/tex]